0852 Narcolepsy Type 1 in a Pediatric Patient with Temporal Lobe Epilepsy. (25th May 2022) - Najimi, Neda; Shahid, Asim; Prero, Moshe
Abstract: Introduction: Narcolepsy type-1 is clinically characterized by irrepressible daytime sleepiness and REM-sleep dissociation, including cataplexy. Cataplexy usually manifests as episodes of brief, symmetrical sudden loss of muscle tone with retained consciousness. It may be difficult to distinguish from seizure activity as they may share overlapping features. We discuss a pediatric patient with temporal lobe epilepsy with co-occuring Narcolepsy Type 1. Report of Cases: A 17-year-old boy with obesity and a history of focal epilepsy secondary to intracranial hemorrhage in the neonatal period status-post right parieto-occipital resection at age 11, presented with worsening fall episodes and feeling of imbalance Following surgery, his seizures improved, but he was having excessive sleepiness. At age 13, he started experiencing episodes of slurred speech, feeling of imbalance, "body heaviness and tongue heaviness" with occasional falls. He denied loss of consciousness, body shaking, stiffening, or incontinence. At age 17, he presented to medical attention due to increasing frequency of such episodes. Physical exam was significant for BMI 42.7 kg/m, Mallampati 4, tonsils 3+ bilaterally, and homonymous hemianopia. Epworth Sleepiness Scale: 22/24. Video EEG was negative for epileptiform discharges despite occurrence of above-mentioned episodes increasing the clinical suspicion of Narcolepsy. Polysomnography revealed sleep latency of 0 minutes, REM latency of 2.6 minutes, and mild OSA. Toxicology screen was negative. MSLT showed mean sleep latency of 1.2 minutes with 3 SOREMPs. CSF orexin could not be obtained due to technical constraints. He was diagnosed with Narcolepsy type-1 and started on Venlafaxine and Methylphenidate with resultant improvement in both daytime sleepiness, and the severity and frequency of cataplexy. However, his feeling of imbalance persisted, prompting repeat video EEG which demonstrated left temporal lobe seizure activity. Anti-epileptic regimen was optimized with improvement in sensation of imbalance. Conclusion: Temporal lobe epilepsy and Narcolepsy Type-1 can have overlapping features that make it difficult to distinguish between the two. While exceedingly rare, the two entities may co-occur. Diagnostic and therapeutic management require coordination between Sleep Medicine and Neurology. While PSG, MSLT, and CSF Orexin can clarify the diagnosis of narcolepsy, neurologic work up should be pursued if symptoms are not completely attributable to Narcolepsy. Support (If Any):